PROBLEM BIROKRASI DALAM MENINGKATAN PELAYANAN PUBLIK PADA SEKRETARIAT DAERAH KABUPATEN MUNA - La Ode Muhammad Elwan (Universitas Halu Oleo, 2019)
The purpose of this study is to find out knowing the problem (inhibiting factors) of bureaucracy in improving the quality of public services at the Muna Regency Regional Secretariat.This study uses a type of qualitative research with descriptive analysis methods in order to describe the problem (inhibiting factors) of bureaucracy in improving the Quality of Public Services at the Muna Regency Regional Secretariat by using data collection methods through interviewing informants and observations.The conclusion of this study is that the problem (inhibiting factors) of bureaucracy in order to improve the quality of public services, namely, human resources that carry out service tasks are not optimal. Because most of those who served in the ministry had a high school education background (high school) which was as many as 19 people or 31.67 per cent. Then the supporting facilities owned by the Muna Regency Secretariat have met service needs, but their utilization is relatively not optimal, this is possible because of limited human resources that have not been able to utilize the facility optimally. Keywords: Bureaucracy, Quality, Public Service